Systematic Literature Review: Reproduksi Struktur Sosial Petani dalam Perspektif Teori Strukturasi Anthony Giddens - Pajar Hatma Indra Jaya; Tri Amal Nazar Saputro; Fahrul (Najah Bestari, 2024)
This study aims to analyze the reproduction of farmers’ social structure through the perspective of Anthony Giddens’ structuration theory using a Systematic Literature Review (SLR) approach. The review highlights the dialectical relationship between farmers as agents and social structures in shaping and sustaining agrarian systems amid social, economic, and agricultural policy transformations. The findings reveal that the reproduction of farmers’ social structures occurs through the inheritance of agrarian values, collective practices based on solidarity, and adaptation to agricultural modernization and global market dynamics. Farmers act as active agents who reinterpret social structures, negotiate power relations, and reproduce social practices that ensure the continuity of traditional farming systems. Structuration theory explains that farmers’ social actions are not merely shaped by structure but also contribute to its transformation. Theoretically, this study strengthens the relevance of structuration theory in analyzing agrarian society, while practically providing a foundation for developing farmer empowerment policies that emphasize agency capacity and the preservation of rural social values.